1978
DOI: 10.2136/sssaj1978.03615995004200050023x
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐exchange Capacity of Clay‐rich Soils in Relation to Organic Matter, Mineral Composition, and Surface Area

Abstract: Regression analyses were used to correlate organic matter, texture and surface area values to the cation‐exchange capacity (CEC) of clay‐rich soils in the lowlands of Quebec. The Ap, Bg and Cg horizons of 11 Gleysolic soils (Aqu‐Suborders) were analyzed for CEC, exchangeable bases and acidity, total and fine clay contents, organic matter, surface area and mineralogical composition. The soils contained illite, chlorite, smectite, and vermiculite in addition to quartz and feldspars. In the Ap horizon, total clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 0 publications
5
20
0
1
Order By: Relevance
“…This suggests that silt and SOM particles contribute to CEC to a lesser extent than clay in this study area. This result is consistent with the findings of Martel et al (1978). Furthermore, the correlations between CEC and soil physicochemical properties are quite different among A and B horizons.…”
Section: Discussionsupporting
confidence: 94%
“…This suggests that silt and SOM particles contribute to CEC to a lesser extent than clay in this study area. This result is consistent with the findings of Martel et al (1978). Furthermore, the correlations between CEC and soil physicochemical properties are quite different among A and B horizons.…”
Section: Discussionsupporting
confidence: 94%
“…These results were consistent with data published by Martel et al(10) who also found SUMBAS to be significantly related to total clay content. The large regression coefficients for CLAY in…”
supporting
confidence: 93%
“…The association between CEC and SSA was rather poor (R 2 = 0.175, p b 0.05, n = 24). Topsoil clay was associated with larger amounts of organic matter and this might be the reason for this poor correlation since SSA was measured on peroxidized samples (Martel et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Goldberg et al (1988) found that in soils of arid regions of California both SSA and the CEC were directly related to the stability of soil aggregates and clay dispersion. It is also known that the cation adsorption increases with increasing contents of fine particles, with the amount of 2 : 1 minerals (Martel et al, 1978), and the contents of soil organic matter (Thompson et al, 1989). Curtin and Smillie (1976) found that both organic matter and fine clay was significantly correlated with CEC in Irish soils from a wide range of parent materials.…”
Section: Introductionmentioning
confidence: 98%